Consensus Update for Systemic Treatment of Atopic Dermatitis - Lee, Ji Hyun; Kim, Jung Eun; Park, Gyeong-Hun; Bae, Jung Min; Byun, Ji Yeon; Shin, Min Kyung; Han, Tae Young; Hong, Seung Phil; Jang, Yong Hyun; Kim, Hye One; Na, Chan Ho; Lew, Bark-Lynn; et al. (Annals of dermatology, 2021)
In 2015, the Korean Atopic Dermatitis Association (KADA) working group published consensus guidelines for treating atopic dermatitis (AD). We aimed to provide updated consensus recommendations for systemic treatment of AD in South Korea based on recent evidence and experience. We compiled a database of references from relevant systematic reviews and guidelines on the systemic management of AD. Evidence for each statement was graded and classified based on thestrength of the recommendation. Forty-two council members from the KADA participated in three rounds of voting to establish a consensus on expert recommendations. We do not recommend long-term treatment with systemic steroids forpatients with moderate-to-severe AD due to the risk of adverse effects. We recommend treatment with cyclosporine or dupilumab and selective treatment with methotrexate or azathioprine for patients with moderate-to-severe AD. We suggest treatment with antihistamines as an option for alleviating clinical symptoms of AD. We recommend selective treatment with narrowband ultraviolet B for patients with chronic moderate-to-severe AD. We do not recommend treatment with oral antibiotics for patients with moderate-to-severe AD but who have no signs of infection. We did not reach a consensus on recommendations for treatment with allergen-specific immunotherapy, probiotics, evening primrose oil, orvitamin D for patients with moderate-to-severe AD. We also recommend educational interventions and counselling for patients with AD and caregivers to improve the treatment success rate. We look forward to implementing a new and updated consensus of systemic therapy in controlling patients with moderate-to-severe AD.